Cultural Heritage Conservation as a Sustainable Source of Genes: Strengthening and Regenerating Cultural Identity in Japan - Le , Vinh An; Nguyen, Thi Kim Nhung (Science and Technology - Recent Updates and Future Prospects Vol. 4, 2024)
The concept of sustainable development has been the main topic of many international conferences. Although many discussions are related to the role of cultural heritage in sustainable development, they develop only on a theoretical level. This study introduces a brief history of the discovery of and conservation efforts to preserve the Nara Palace Site in Japan, which brought about the recognition of this heritage site as a World Cultural Heritage location by UNESCO in 1996. Accordingly, the 1994 Nara Document on Authenticity plays an important role in contributing to Japanese cultural heritage conservation achievements, with the expansion of cultural diversity and heritage diversity and the concepts of values and authenticity, which proposed a new orientation in terms of awareness and openness to develop a broader vision when identifying architectural heritage values. The unifying characteristic of the wooden architectural heritage of Asian countries is the creation of structures from a variety of timbers using specific tenon-jointing techniques. In addition to forced changes, due to human repair and renovation activities, wooden structures also show their own changes due to external factors that affect them and the unavoidable effects of material decomposition. Against this background, we first discuss the newly proposed concept of so-called "architectural heritage DNA" and its potential structure, providing a simple formula for appraising the authentic values of architectural heritage conservation works. The viewpoints expressed in this paper are based on the most common concepts of these international conventions but are interpreted in a novel, understandable, practical, and highly applicable approach suited to both the current socio-political situation and future scenarios. To successfully conserve the cultural genetics of each ethnic community, it is necessary that "architectural heritage DNA" needs to be assumed and regenerated for the further cultural development of each country.